Ventricular Septal Rupture in ST-Elevation Myocardial Infarct in Low Resource Setting: a case series - Suryono Suryono; Naesilla Naesilla; Jarwoto Roestanajie; Dwi Ariyanti; Pipiet Wulandari (Jurnal Kardiologi Indonesia, 2020)
Background: The mortality rate caused by myocardial infarct (MI) escalates in the presence of ventricular septal rupture (VSR). This article aimed to analyze clinical factors that might be valuable as predictors of VSR. Case Illustration: We found and presented six documented post-infarction VSR out of 1,613 MI cases between January 2015 to December 2019. Conclusion: Based on the analysis, clinicians should be aware of these factors as they were potential to be the predictors: advanced age, first MI, anterior location of the infarct, infranodal conduction disorder, no reperfusion treatment, high systolic blood pressure on admission, and no smoking history.